External Moderation of Reactor Core Neutrons for Optimized Production of Ultra-Cold Neutrons - Graham Medlin; Ekaterina Korobkina; Cole Teander; Bernard Wehring; Eduard Sharapov; Ayman I. Hawari; Paul Huffman; Albert R. Young; Grant Palmquist; Matthew Morano; Clark Hickman; Thomas Rao; et al. (Journal of Nuclear Engineering)
The ultra-cold neutron (UCN) source being commissioned at North Carolina State University’s PULSTAR reactor is uniquely optimized for UCN production in the former graphite-filled thermal column outside of the reactor pool. The source utilizes a remote moderation design, which is particularly well suited to the PULSTAR reactor because of its high thermal and epithermal neutron leakage from the core face. This large non-equilibrium flux from the core is efficiently transported to the UCN source through the specially designed beam port in order to optimize UCN production at any given reactor power. The increased distance to the source from the core also greatly limits the heat load on the cryogenic system. A MCNP (Monte Carlo N-Particle) model of this system was developed and is in good agreement with gold foil activation measurements using a test configuration as well as with the real UCN source’s heavy water moderator. These results established a firm baseline for estimates of the cold neutron flux available for UCN production and prove that remote moderation in a thermal column port is a valuable option for future designs of cryogenic UCN sources.